The attitudes of professionals towards implementation of the registry of offenders of sexual abuse of juveniles - Petković Nikola; Pavlović Zoran; Stevković Ljiljana (Temida)
The sexual victimization of children has always drawn great attention from experts and criminal policy makers due to the nature of the violent behavior and the developmental specific characteristics of the victims which enjoy special criminal law protection in a developed society. The high dark number and sex offender recidivism, as referenced by the frequent media reports about new cases of sexual violence towards the youngest memebers of society, highlight the need to search for the most appropriate social response to this form of sexual offending. The establishment of a register of convicted sex offenders for acts of sexual violence committed against minors, as one approach with a primary special preventive purpose, found its application in criminal law theory and practice of the Republic of Serbia. The aim of the paper is to present the results of an attitudinal survey of professionals employed in the field of justice and social welfare in the Republic of Serbia on the provisions of the special measures to prevent the commission of crimes of sexual abuse against juveniles and the establishment of the register of sex offenders.